The Application of the Collective Agreement and Personnel Administration - Gagné, Jean (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1949)
Employers' attitude towards workers' unions as negotiating units of the collective labour agreement